Pengaruh Penyuluhan Kesehatan Media Leaflet Terhadap Pengetahuan Pasien TB Paru di RS Kartika Kasih Sukabumi - Laura Cahya Kamilah; Irawan Danismaya; Egi Mulyadi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. As is the case with patients at the Kartika Kasih Sukabumi Hospital, there are patients who are readmitted to the hospital for treatment because they do not regularly take anti-tuberculosis medication so they experience complaints again that really disrupt their daily quality of life. Leaflet media, as a simple and easy to carry tool, is still an option in health promotion. Objective: This research was conducted to determine the effect of health education through leaflet media on the knowledge of pulmonary TB patients at Kartika Kasih Hospital, Sukabumi. Research Method: using Quasi Experimental with One Group Pre and Post Test design with purposive sampling technique. The samples taken in this research were 15 people. Data analysis used the Paired t test. This research conducted health education about pulmonary TB using leaflet media. Results: obtained after counseling there was an increase in the average knowledge from a score of 6.87 to 10.47. Conclusion: there is a significant influence of health education through leaflet media on the knowledge of pulmonary TB patients at Kartika Kasih Hospital Sukabumi. Suggestion: respondents are advised to increase their knowledge in order to maintain their health so that complications do not occur.